Kritik und Engagement in der Sozialen Arbeit Gesellschaftliche Transformation durch Partizipation und professionelle Praxis - Berc, Gordana; Heimgartner, Arno; Lauermann, Karin; Reicher, Hannelore; Stuhlpfarrer, Elena (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2024)
The anthology stands for critical-political and transformative social work. In twelve contributions in German and four in English, the authors discuss three overarching goals: affordable housing, an engaged society and an economy of solidarity. They look at problems such as poverty and the precarisation of working conditions and offer answers in a critical professionalism and in the voices of the addressees.